Child poverty in the OECD Trends, determinants and policies to tackle it - Thévenon, Olivier (OECD Publishing, 2018)
This paper provides an overview of the main trends in child income poverty since the mid-2000s, and explores to what extent child poverty trends are linked to demographic, policy and/or labour market changes. Trends in poverty and the standard of living of children in low-income families since the onset of the Great Recession are also closely examined: nearly 1 in 7 children is income-poor in the OECD, and child poverty increased in almost two/thirds of OECD countries with the Great Recession. About 1 in 10 children across the OECD live in a family with a standard of living below the 2005 poverty line. Children in low-income families experienced a decline in their standard of living in many countries, with the largest decline among families with the smallest incomes
Keywords: Employment; Social Issues/Migration/Health